The Effect of Profitability, Solvency, and Company Growth on Corporate Social Responsibility Disclosure - Syfa Ratu Anjelita; Fahrul Imam Santoso (CV Edujavare Publishing, 2026)
This study aims to examine the influence of Company Profitability, Solvency, and Growth on Corporate Social Responsibility Disclosure. The sample of this study is 19 companies listed on the Indonesia Stock Exchange using the purposive sampling method. The analysis technique used is multiple linear regression. The results of the study show that Profitability and Company Growth partially or simultaneously do not have a significant effect on Corporate Social Responsibility Disclosure, while Solvency itself has a significant effect on Corporate Social Responsibility Disclosure. The Adjusted R Square value of 0.109 indicates that the three independent variables are only able to explain 10.9% variation in CSR disclosure. It was concluded that the company's decision to disclose CSR was not influenced by the company's financial condition, but rather the fulfillment of regulations and corporate social responsibility.